HUBUNGAN PENGETAHUAN GIZI IBU, ASUPAN ZAT BESI, ZINK, ASI EKSKLUSIF, DAN BBLR DENGAN KEJADIAN STUNTING PADA BALITA USIA 6-59 BULAN DI WILAYAH KERJA PUSKESMAS ANAK AIR KOTA PADANG - Nurhamidah, Nurhamidah; Adfar, Tika Dwita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Stunting is a chronic nutritional problem caused by malnutrition over a long period of time due to food intake that is not in accordance with nutritional needs. This stunting problem begins to occur when the baby is still in the womb and will begin to be seen when the child reaches the age of two. Stunting is influenced by the health status of adolescents, pregnant women, the diet of toddlers, as well as economic, cultural, and environmental factors such as sanitation and access to health services. This study was conducted to determine the relationship between maternal nutrition knowledge, iron intake, zinc, exclusive breastfeeding, and low weight with the incidence of stunting in toddlers aged 6-59 months.The type of research used is descriptive-analytical with a Cross-sectional research design.The sampling technique uses a simple random sampling technique of 93 respondents. Data on maternal nutrition knowledge, iron intake, zinc, exclusive breastfeeding, and BBLR using questionnaires and SQ-FFQ forms. Data analysis using statistical test Chi-Square test.From the results of the study, it was found that there were 33.3% of mothers who had stunting toddlers, 64.52% of mothers who had less nutritional knowledge, 64.52% of iron intake in toddlers lacking, 55% of zinc intake in toddlers lacking, 12.90% of mothers did not provide exclusive breastfeeding to their toddlers, and 11.8% of toddlers were low birthweight. From the results of statistical tests, it was found that there was a significant relationship between maternal nutritional knowledge, iron intake, zinc with the incidence of stunting, and there was no relationship between exclusive breastfeeding and low weight with the incidence of stunting. Keywords: knowledge, iron intake, zinc, exclusive breastfeeding, low weight, stunting